2004
DOI: 10.2478/bf02476198
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and the structure elucidation of N,O-diacetyl derivative of cyclic 3-hydroxymelatonin

Abstract: Abstract:Melatonin was subjected to an oxidation to give 3-hydroxymelatonin. All spectroscopic data for this compound were collected. Ab initio calculations for both possible configurations were performed. X-ray data on N ,O-diacetyl derivative of 3-hydroxymelatonin allowed the unambigous structure determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…In this reaction, C3‐OHM scavenges two ABTS cation radicals to form AFMK. A method for the synthesis of C3‐OHM from melatonin was recently published [92]. Both C3‐OHM and AFMK have been identified in the same urine samples of mice [88].…”
Section: Metabolism and Metabolites Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…In this reaction, C3‐OHM scavenges two ABTS cation radicals to form AFMK. A method for the synthesis of C3‐OHM from melatonin was recently published [92]. Both C3‐OHM and AFMK have been identified in the same urine samples of mice [88].…”
Section: Metabolism and Metabolites Of Melatoninmentioning
confidence: 99%
“…It has been speculated that C3‐OHM may be useful in disorders related to cholinergic transmission impairment, e.g. Alzheimer's disease [92]. C3‐OHM has been found capable of reducing two ABTS cation radicals per molecule [91] and preventing oxidative DNA damage caused by Fenton regents [133].…”
Section: Functions Of Melatonin Metabolitesmentioning
confidence: 99%
“…Using cyclic 3‐hydroxymelatonin (c3OHM) synthesized by Siwicka et al. , Tan et al. found it to be at least as effective as melatonin itself in scavenging the .…”
Section: Melatonin Reduces Oxidative Stress: the Machinery And The Mementioning
confidence: 99%
“…However, there are indications that when this reaction is carried out at −78°C and Bengal rose is used as a photosensitized dye, then cyclic 3‐hydroxymelatonin 10 can be isolated as the main product [27]. Indeed, we found that this slightly modified procedure can effectively be applied for the preparation of cyclic 3‐hydroxymelatonin 10 on 100 mg scale [28]. The structure of this compound has also been unambiguously proven with X‐ray crystallography [28].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we found that this slightly modified procedure can effectively be applied for the preparation of cyclic 3‐hydroxymelatonin 10 on 100 mg scale [28]. The structure of this compound has also been unambiguously proven with X‐ray crystallography [28].…”
Section: Methodsmentioning
confidence: 99%